DEPLOYMENT OF AUTOMATION TECHNOLOGIES IN FINANCIAL REPORTING PRACTICES AMONG MULTINATIONAL COMPANIES IN NIGERIA (Journal of Contemporary Issues in Accounting, 2026)
This study investigated the deployment of automation technologies in financial reporting practices among multinational companies operating in Nigeria, focusing on their effects on timeliness, accuracy, and compliance with international financial reporting standards (IFRS). The rapid integration of technologies such as Robotic Process Automation (RPA), Artificial Intelligence (AI), and cloud-based systems has revolutionized global financial reporting, yet their practical application in Nigeria remains underexplored. A quantitative research design was adopted using structured questionnaires administered to finance professionals in 5 multinational companies, from which 38 valid responses were obtained. Descriptive statistics and regression analysis (via E-view 9.0) were used to analyze the data. Findings indicate that automation technologies significantly enhance the timeliness and accuracy of financial reports and improve compliance with IFRS. However, challenges such as infrastructural limitations, skill gaps, resistance to change, and data security concerns persist. The study concludes that despite these challenges, automation offers considerable potential to strengthen financial reporting reliability and transparency in Nigerian multinational enterprises. The results provide valuable insights for multinational managers, regulators, technology providers, and researchers interested in financial technology adoption in emerging markets.
Keywords: Accuracy; Automation Technologies; Financial Reporting; Multinational Companies; Timeliness